2017
DOI: 10.2147/opth.s143756
|View full text |Cite
|
Sign up to set email alerts
|

Combined phacocanaloplasty for open-angle glaucoma and cataract: 12 months results

Abstract: Purpose of the studyTo evaluate efficacy, safety, and success rates of canaloplasty combined with phacoemulsification and intraocular lens implantation in patients with open-angle glaucoma (OAG) and visually significant cataract.Patients and methodsA prospective interventional noncomparative case series carried out in Minia University Hospital from April 2015 to October 2016 on 20 eyes of 18 patients who had visually significant cataract and primary OAG. All the cases had combined phacocanaloplasty. Preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…29 Increasing the length of the dilated portion of SC improves outflow, as observed with treatment using SC scaffolds. 19,20 Genaidy et al 30 showed that canaloplasty successfully reduced the IOP from 25.2 6 1.009 mm Hg before surgery to 15.9 6 0.7 mm Hg at 1 year after surgery in eyes with primary open angle glaucoma. In our study, both SCAR(mean) and IOP changed synchronously in the first 15-minutes post-WDT and returned to baseline by 60-minutes post-WDT.…”
Section: Discussionmentioning
confidence: 99%
“…29 Increasing the length of the dilated portion of SC improves outflow, as observed with treatment using SC scaffolds. 19,20 Genaidy et al 30 showed that canaloplasty successfully reduced the IOP from 25.2 6 1.009 mm Hg before surgery to 15.9 6 0.7 mm Hg at 1 year after surgery in eyes with primary open angle glaucoma. In our study, both SCAR(mean) and IOP changed synchronously in the first 15-minutes post-WDT and returned to baseline by 60-minutes post-WDT.…”
Section: Discussionmentioning
confidence: 99%
“…found that canaloplasty (SC dilatation program) successfully decreased the IOP after 12 months in eyes with POAG. [ 26 ] In our study, the IOP peak after 20 min of head-down position might be explained by the collapse of the SC lumen of increased parasympathetic nervous activity.…”
Section: Discussionmentioning
confidence: 57%
“…found that reduction in SC dimensions in POAG eyes may account for approximately half of the decrease in outflow facility 26 . The SC has attracted considerable interest in recent years 27 . In this study, SCAR was found expanded and was correlated with the activation of SNS (LF/HF index).…”
Section: Discussionmentioning
confidence: 99%